The second leafhopper of the subfamily Ledrinae (Hemiptera, Cicadellidae) in mid-Cretaceous Burmese amber. (June 2021) - Chen, Jun; Jiang, Hui; Shang, Tingting; Zhang, Lixia; Zheng, Yan; Zhang, Qianqi; Zhang, Haichun
Abstract: The cicadellid subfamily Ledrinae known in the Mesozoic is represented by two monotypic genera erected on six compression fossils from the Lower Cretaceous Crato Formation in Brazil, and the monotypic genus Qilia based on an adult leafhopper in mid-Cretaceous Kachin amber from northern Myanmar. We herein describe and illustrate a new female ledrine in Kachin amber, based on which a new genus and species, Duyana electronica gen. et sp. nov., is established. Duyana gen. nov. shares a series of features with the genus Qilia, but is distinguishable from the latter with some novel morphological characteristics. The hitherto definite cicadellid recorded in the Mesozoic are very scarce, and our find provides new information on early disparity of this mega-diverse insect lineage.